2013
DOI: 10.1111/trf.12106
|View full text |Cite
|
Sign up to set email alerts
|

Addition of ascorbic acid solution to stored murine red blood cells increases posttransfusion recovery and decreases microparticles and alloimmunization

Abstract: These data indicate that the addition of ascorbic acid solution to RBCs during storage has a beneficial effect on recovery and immunogenicity of RBCs, but not cytokine induction. The addition of ascorbic acid (or other antioxidants) to human RBCs may have beneficial effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 40 publications
(87 reference statements)
3
50
0
1
Order By: Relevance
“…32 In vivo studies in mice have shown that vitamin C supplementation can improve storage as measured by 24-h recovery. 33 The generation of products of lipid oxidation not only gives insight into underlying RBC storage biology, but may in themselves represent a biologically significant component of transfused RBCs. Among the lipid oxidation products that were observed to both increase with…”
Section: Discussionmentioning
confidence: 99%
“…32 In vivo studies in mice have shown that vitamin C supplementation can improve storage as measured by 24-h recovery. 33 The generation of products of lipid oxidation not only gives insight into underlying RBC storage biology, but may in themselves represent a biologically significant component of transfused RBCs. Among the lipid oxidation products that were observed to both increase with…”
Section: Discussionmentioning
confidence: 99%
“…The samples were also stained with a primary Ab, MIMA29, an anti-Fy6 Ab, or an anti-GPA Ab at a concentration of 1 mg/100 ml in FACS buffer (2% BSA, 0.9% EDTA in PBS), then with a secondary Ab, goat anti-mouse Igs (BD Biosciences Pharmingen), diluted 1:100 in FACS buffer, as outlined previously (31). The samples were also stained with Rat anti-TER119 (BD Biosciences Pharmingen), also diluted to 1:100 with FACS buffer; Rat IgG2b k (BD Biosciences Pharmingen) Abs were used as an isotype-matched control.…”
Section: Rbc Characterizationmentioning
confidence: 99%
“…Unit age and storage solution were included as study variables because RBCs undergo a number of physical and biochemical changes during their storage that may be pro-inflammatory to a transfusion recipient, as observed in murine models (Hendrickson et al, 2010(Hendrickson et al, , 2011Stowell et al, 2013).…”
Section: Methodsmentioning
confidence: 99%